Sharing good practice and encouraging community cohesion online: a programme of tutor-led online events for Open University tutors. (2nd January 2022) - Haresnape, Janet M.; Aiken, Fiona J.; Wynn, Nirvana C.
ABSTRACT: This study explored the extent to which distance learning tutors found sharing practice through participating in a tutor-led online programme of online events helped them to develop as practitioners and hence support students more effectively. The regular online sessions, delivered by tutors for tutors, was a staff development initiative introduced at the Open University (OU) to (i) provide tutors with opportunities to share good practice with a view to improving their online interactions with students, and (ii) help nurture a sense of community, providing a supportive situated learning environmentwhich fosters peer support and in which tutors can share ideas and concerns. Quantitative and qualitative analysis of feedback obtained through surveys demonstrated the programme succeeded in providing opportunities for distance learning tutors to share good practice in a friendly supportive environment, hence relieving some of the isolation they feel. Moreover, it helped nurture community cohesion. Similar programmes could help strengthen tutor communities and provide valuable opportunities for sharing concerns and good practice in any institution where tutors feel isolated. Examples might include institutions where much tuition is delivered online, where staff are located on different sites or where many staff have insecure contracts and therefore building community spirit is likely to be challenging.